Pembelajaran Menulis Teks Ulasan Menggunakan Metode Suggestopedia Berbantuan Media Powtoon Pada Peserta Didik Kelas VIII SMPN 10 Bandung - Hafsa Zikri Nasati; Dheni Harmaen; Rendy Triandy (FKIP, Universitas Palangka Raya, 2024)
In order to achieve a learning process, educators are required to have a creative spirit in planning and implementing the learning. Therefore, one thing that educators need to do is to choose the right, creative, and innovative method. By choosing the right method, educators can achieve success in conveying material to students. In this study, the authors chose a quantitative method for the topic of the suggestopedia learning method assisted by powtoon media to help expedite the learning process. After doing the research, it can be concluded that the suggestopedia method assisted by powtoon media is effective in learning to write review texts, this method can also improve student learning outcomes. The average pretest score in the experimental class was 31.30 and it increased in the posttest to 84.57. Whereas in the control class, the average score in the pretest activity was 28.04 and experienced an increase in the posttest activity to 55.43. But the average of the experimental class is greater than the average of the control class. Based on the output obtained from the results of the Wilcoxon test analysis, the value of Sig. (2-tailed) 0.000 < 0.005. This shows that the average increase of the experimental class is much higher than that of the control class.